Mencermati Kisah Dipilihnya Matias Dari Spiritualitas Kaum Pentakostal - Kosma Manurung (Sekolah Tinggi Teologi Syalom Bandar Lampung, 2022)
Both in organizations and in social life, the existence of a leader is absolutely necessary to ensure the maintenance of order and peace in life. The Bible gives various descriptions of the election of a person to become a leader, for example Joseph who was chosen as a leader because he was able to interpret the dreams of Pharaoh or Saul who became king of Israel by lot. This article intends to reinterpret the story of the choice of Matthias to replace Judas Iscariot in Acts 1:15-26 from the Pentecostal spirituality frame. By using descriptive research methods and support from literature studies, it is hoped that this research will be able to provide a strong explanation of the variety of leadership choices in the biblical picture, the story of the election of Matthias, and the meaning of the Pentecostals related to this story. It was found that for the Pentecostals, the story of the election of Matthias to replace Judas Iscariot was a decision of God whose election was carried out in God's way. This story is also interpreted as God's answer to restore the elect. Abstrak Baik dalam organisasi maupun dalam kehidupan bermasyarakat keberadaan pemimpin mutlak perlu untuk memastikan terjaganya ketertiban dan kedamaian hidup. Alkitab memberikan berbagai gambaran terpilihnya seseorang menjadi pemimpin, seumpama Yusuf yang terpilih jadi pemimpin karena mampu menafsirkan mimpi Firaun ataupun Saul yang menjadi raja Israel lewat undian. Artikel ini bermaksud memaknai ulang kisah dipilihnya Matias mengantikan Yudas Iskariot dalam Kisah Para Rasul 1:15-26 dari bingkai spritualitas Pentakostal. Dengan menggunakan metode penelitian deskripsi dan dukungan dari kajian literatur, penelitian ini dirahapkan mampu memberikan penjelasan yang kuat tentang ragam pemilihan pemimpin dalam gambaran Alkitab, kisah pemilihan Matias, dan pemaknaan kaum Pentakostal terkait kisah ini. Didapati bahwa bagi kaum Pentakostal, kisah dipilihnya Matias mengantikan Yudas Iskariot ini merupakan keputusan Allah yang pemilihannya dilakukan dengan cara Allah. Kisah ini juga dimaknai sebagai jawaban Allah untuk memulihkan umat pilihan.